Kepemimpinan Dimulai dari Kelas: Langkah Kecil Membangun Lingkungan Belajar Positif di PAUD - Husnul Hatimah; Khadijah; Helyatul Khodizah; Maulida Norsyifa; Aslamiah; Celia Cinantya (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The quality of early childhood education is strongly influenced by the leadership role of teachers in the classroom. Teachers not only act as educators but also as leaders who shape a positive, safe, and engaging learning environment. This study uses a library research approach to examine literature related to classroom leadership, character development in early childhood, and strategies to build a supportive learning atmosphere. Findings highlight the importance of small actions by teachers—such as fostering positive discipline, showing appreciation, providing emotional safety, and involving children in classroom decisions—which significantly contribute to children’s academic and emotional growth. Role-playing methods are also effective in instilling leadership values from an early age. Thus, leadership starts in the classroom, becoming a crucial step in preparing strong and character-driven future generations